Biological Mechanisms of Atypical and Melancholic Major Depressive Disorder - Tarasov, Vadim V.; Ivanets, Nikolay N.; Svistunov, Andrey A.; Chubarev, Vladimir N.; Kinkulkina, Marina A.; Tikhonova, Yuliya G.; Syzrantsev, Nikita S.; Chubarev, Ivan V.; Muresanu, Cristian; Somasundaram, Siva G.; Kirkland, Cecil E.; Aliev, Gjumrakch (Current Pharmaceutical Design, 2021)
Background: This review summarizes recent findings in molecular biology and neuroimaging and their applicability to the classification and identification of depression. We discuss whether there is reliable evidence that could become a basis for biomarkers or subtyping that may enhance our understanding of the biological foundations of depression and may be useful for clinical practice with respect to diagnosis and prognosis as well as the selection of treatments. Objective: The purpose of this investigation is to present molecular mechanisms that contribute to different origins of depressions that could prove useful in the daily psychiatric clinic-based practices. Methods: The authors have analyzed and summarized electronic publications available in PubMed, Science Direct, Google Scholar, and Scopus. Results: The introduction of molecular diagnostic methods into medical practice is a promising method to improve the accuracy of the diagnosis of depression in clinical settings. The literature analysis revealed structural changes in some areas of the brain, its neuroplasticity, as well as changes at the molecular, epigenetic, and genetic levels. However, there are no current reliable biomarkers for differential diagnosis of the types and subtypes of depression. Conclusion: Major depressive disorder is a biologically and genetically heterogeneous disorder. Given its complexity, subtyping is worthwhile to identify biological bases of conditions. The literature review provides ample findings that reveal possible underlying biological mechanisms associated with atypical and melancholic depression. Additional focused research should be continued with respect to the molecular and genetic biology of different types of depression. There already are promising findings, but additional research to define biologically based depressive subtypes is needed and worthwhile.
Keywords: metabolomics